(untitled) (Diversity Research: Journal of Analysis and Trends, 2026)
In modern business environments, the effectiveness of financial decision-making largely depends on the quality, reliability, and transparency of accounting information. Investment property has become an important component of corporate assets and plays a significant role in generating rental income and capital appreciation. Accurate accounting of investment property is therefore essential for ensuring the reliability of financial statements and supporting informed managerial and investment decisions. International Financial Reporting Standards, particularly IAS 40 Investment Property, provide a framework for the recognition, measurement, and disclosure of investment property in financial reporting. However, practical implementation of these standards often presents several challenges related to valuation methods, classification of assets, and the availability of reliable market data. This study examines the role of investment property accounting systems in improving financial decisionmaking and analyzes the main issues associated with their application in practice. The research also explores theoretical and methodological approaches to investment property accounting and highlights the importance of fair value measurement in enhancing financial reporting transparency. Based on the analysis, several recommendations are proposed for improving investment property accounting systems in order to strengthen the reliability of financial information and support effective financial decision-making.